Digital Tax Compliance: Examining E-Filing, Tax Knowledge, and Income Level Among Telkom Property Regional IV Employees in Central Java & Yogyakarta, Indonesia - Rasyida, Quinnandiva Zahra; Badjuri, Achmad (Golden Ratio of Finance Management, 2025)
This study aimed to test and analyze the implementation of the e-filling system, tax understanding, and income level on individual taxpayer compliance with tax socialization as a moderating variable. This study was conducted on Telkom Property Regional IV Central Java employees and the Special Region of Yogyakarta. This study uses a quantitative method with research samples taken using the Convenience Sampling Technique. In this technique, researchers obtained one hundred and five samples. The data analysis techniques used in this study are multiple linear and moderated regression analyses. The results of the analysis in this study can be concluded that the implementation of the e-filling system, tax understanding, and income level have a significant effect on taxpayer compliance. In this study, tax socialization has been proven unable to strengthen the relationship between the implementation of the e-filling system and tax understanding on taxpayer compliance. However, tax socialization can moderate the level of income on taxpayer compliance.